Analisis Tingkat Kebisingan Pada Kawasan Sekolah Dasar Negeri Pasar Lama I Kota Banjarmasin - Dyah Pradhitya Hardiani; Emma Ruhaidani; Elia Anggarini (AGREGAT, 2022)
The increase in traffic flow that occurs in addition to causing traffic jams has an impact on air pollution and sound pollution. Noise caused by traffic can cause health problems in humans who are exposed to it and can be achieved in stages from physiological disorders, communication disorders, balance disorders, and deafness. Noise that occurs in the school environment that will interfere with learning activities and student comfort. The purpose of this study was to determine the levels in the SDN Pasar Lama 1 Banjarmasin and to know the composition of the traffic flow that passes through Jl. S. Parman, Banjarmasin City. The data needed in this study is primary data, namely traffic volume data and the exact data at the observation location. Traffic data and data are taken simultaneously for 1 day at 08.00 WITA – 10.00 WITA, with a time span of 10 minutes. The intensity is taken in the study room at a distance of 50 meters from the road. The tools used in this research are hand counter, stopwatch, and sound level meter. From the results of the analysis that has been carried out, the total traffic volume on JL S. Parman is 17,810 smp/hour with a motorcycle percentage of 66.47%. While the highest value was obtained at 68.88 dB and the lowest was 61.24 dB. From this result, it is located in a location that exceeds the standard stipulated in the Regulation of the Minister of the Environment No. 48 of 1996 is 55 dB. Additional handling of the school environment is needed to help control levels that occur by adding natural or artificial barriers. This is done so that what happens does not affect the comfort of students in learning activities. Handling can be in the form of artificial barriers and natural barriers.